2022
DOI: 10.3390/ijerph192214661
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Well-Being and Associated Factors during the COVID-19 Pandemic: A Cross-Sectional Study in Hong Kong, China

Abstract: School teachers have faced many challenges due to the coronavirus disease-2019 (COVID-19) pandemic and public health-related containment measures. Recent studies have demonstrated high levels of stress and mental health issues among school teachers. To better understand teacher well-being and inform practices to support them in the face of the ongoing pandemic, we aimed to assess perceived stress, well-being and associated factors among school teachers in Hong Kong, China. For this cross-sectional study, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 82 publications
(102 reference statements)
5
12
0
Order By: Relevance
“…While no adequate explanation is offered by the researchers with respect to the observed elevated TWB rates in different stages of the pandemic, these findings strikingly run counter to those reported in (i) [112], where substantially self-reported increased levels of stress (72%) and burnout (57%) and an inability to strike a good work-family balance impeded online teaching efficacy required amidst volatile COVID-19 circumstances; (ii) Wong et al's [113] small-scale study with primary English language teachers who explicitly reported on the insurmountable emotional toll they had experienced due to the swift COVID-19-induced instructional shift that often resulted in feelings of heightened anxiety, absolute distress, and despair; and (iii) [114], where 77.2% of Australian teachers' responses indicated that high levels of stress and low levels of positive feelings such as joy, positivity, and contentment in their work during the COVID-19 pandemic negatively impacted their well-being and self-efficacy. In line with the studies [110,111], self-reported high TWB levels were also reported in another two parallel studies in our sample, which were primarily associated with online teaching competency skills and the teacher self-belief system in the virtual teaching paradigm, illustrating that: (a) satisfactory TWB levels in terms of increased selfperceived work satisfaction and work-related sense of coherence were positively related to enhanced online teaching self-efficacy skills [115] and (b) positive teacher self-assessments (75.25%) with respect to their implementation competency and success with online teaching and learning were linked to elevated TWB and diminishing levels of emotional exhaustion and stress overall [116]. Conversely, low TWB levels only moderately affected Malaysian teachers' persistence to teach online as compared with the critical role of e-learning system quality and instructor self-efficacy [117].…”
Section: B Studies In Primary and Secondary Educationsupporting
confidence: 91%
See 3 more Smart Citations
“…While no adequate explanation is offered by the researchers with respect to the observed elevated TWB rates in different stages of the pandemic, these findings strikingly run counter to those reported in (i) [112], where substantially self-reported increased levels of stress (72%) and burnout (57%) and an inability to strike a good work-family balance impeded online teaching efficacy required amidst volatile COVID-19 circumstances; (ii) Wong et al's [113] small-scale study with primary English language teachers who explicitly reported on the insurmountable emotional toll they had experienced due to the swift COVID-19-induced instructional shift that often resulted in feelings of heightened anxiety, absolute distress, and despair; and (iii) [114], where 77.2% of Australian teachers' responses indicated that high levels of stress and low levels of positive feelings such as joy, positivity, and contentment in their work during the COVID-19 pandemic negatively impacted their well-being and self-efficacy. In line with the studies [110,111], self-reported high TWB levels were also reported in another two parallel studies in our sample, which were primarily associated with online teaching competency skills and the teacher self-belief system in the virtual teaching paradigm, illustrating that: (a) satisfactory TWB levels in terms of increased selfperceived work satisfaction and work-related sense of coherence were positively related to enhanced online teaching self-efficacy skills [115] and (b) positive teacher self-assessments (75.25%) with respect to their implementation competency and success with online teaching and learning were linked to elevated TWB and diminishing levels of emotional exhaustion and stress overall [116]. Conversely, low TWB levels only moderately affected Malaysian teachers' persistence to teach online as compared with the critical role of e-learning system quality and instructor self-efficacy [117].…”
Section: B Studies In Primary and Secondary Educationsupporting
confidence: 91%
“…Other elements associated with solid school organization reported in relevant studies to sustain and boost TWB levels within the context of the COVID-19 pandemic were: (i) the existence of an organized, supportive school environment as a critical job resource and enabler of TWB that impacts teachers' fulfillment of basic psychological needs for autonomy, ensures collaboration with colleagues and accomplishment in pandemic emergency remote teaching (ERT) by prescribing the principles for effective distance education teaching practices [104], and promotes teachers' creative teaching self-efficacy by enhancing their dispositional joy and general positive affect while reducing general negative affect [144]; (ii) empowering leadership that was found to be associated with lower levels of job stress and higher levels of job well-being and perceived organizational support [145], enabling preschool teachers to link their personal goals to organizational goals, motivate and guide them to better achieve their mission with organizational support, and thus achieve a high level of well-being; (iii) the allocation of low teacher workloads by the school administration, which was found to be positively associated with work satisfaction and work-related coherence, leading to enhanced TWB COVID-19 rates in [115]; (iv) the adoption of schoolbased TWB interventions within the COVID-19 era, as documented in three action-oriented studies in our sample, which were directed at the exploration of TWB improvement using peer support in digital settings [146], the implementation of in-service professional training TWB sessions aiming at reducing teachers' psychological distress [147], and emergent mindfulness and cognitive reframing TWB approaches with reported increased gains in teachers' resilience and psychological well-being in times of crisis [148]. Provision of training support in ERT-related issues and teachers' eagerness to seek religious and spiritual support to regain their well-being by overcoming the numerous pre-and post-pandemic challenges and difficulties were reported by [149], with self-reported spirituality being only indirectly associated with TWB enhancement and teachers' overall mental health in one study [127].…”
Section: B Twb Levers During the Covid-19 Eramentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study of 1,640 childcare providers and early educators linked both lower salaries and additional workplace demands to elevated depressive symptoms (Roberts et al , 2019). It is important to note that these financial stressors were further exacerbated by the COVID-19 pandemic (Batt et al , 2022; Lau et al , 2022), which was impacting the workforce during the time these data were collected.…”
Section: Discussionmentioning
confidence: 99%